Religion and Culture: Walisongo Cultural Da'wah in Maintaining Religion - Kurniawati, Hikma; Endhar Rosidatul Usna; Muhammad Miftah; Zeni Rahmawati (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The lack of awareness and ability of today's preachers to unite diversity as Walisongo does mean that there are still gaps in understanding and implementing the values of inter-religious harmony. This research aims to explore the role and methods of Walisongo da'wah in promoting inter-religious harmony, as well as to investigate the possible application of their da'wah messages in an increasingly complex context of diversity. The research methods used include literature study, historical data analysis with descriptive analysis techniques. The research results show that the inclusive and dialogical approach implemented by Walisongo has a positive impact in uniting religious and cultural diversity. Today's preachers can adopt the strategies implemented by Walisongo, such as approaches based on local wisdom and community empowerment, to strengthen harmony and solve gaps in understanding religion. Therefore, the results of this research confirm that Walisongo da'wah provides a relevant and effective model in responding to the challenges of religious and cultural diversity, and can be a guide for today's preachers in building a more harmonious and inclusive society.